Effect of Stroking on Serotonin, Noradrenaline, and Cortisol Levels in the Blood of Right- and Left-Pawed Dogs - Karpiński, Mirosław (Animals (Basel), 2021)
SIMPLE SUMMARY: The endocrine balance, reflected in the level of neuromodulators, is necessary for maintenance of homeostasis and facilitates adaptation to stressful conditions. An important role in processing the information reaching the brain is played by the asymmetric specialization of cerebral hemispheres referred to as laterality. The domestic dog shows preference of the forelimb determined by the predominance of the activity of the right or left brain hemisphere. Investigations of various animal species indicate that the left-brain hemisphere is involved in the control of unchanging stimuli or repetitive actions, while the right hemisphere is specialized in the quality of emotional reactions such as aggression or fear. A skillful observation of combined behavioral and physiological symptoms of stress in dogs provides better insight in the dog’s perception of veterinary care, and any means of reduction of the stress level is highly recommended, as it improves animal’s welfare. The results of the present study indicate that dogs’ laterality and sex affect the stress response and stroking can relieve stress. The level of the analyzed neuroregulators indicating intensification of stress or adaptation to stress conditions was higher in the males and in the right-pawed dogs. Our results confirm our assumptions that right-pawed dogs are better adapted to stressful conditions. ABSTRACT: It has been assumed that stroking relieves stress responses in dogs, and dogs with the activation of the left-brain hemisphere (right-pawed) may show better adaptation to stress conditions. The aim of the study was to determine whether the stroking stimulus induced changes in the level of selected neuroregulators in dogs’ blood and whether these changes depended on the sex and the predominance of the activity of one of the brain hemispheres. The study involved 40 dogs of various breeds and both sexes. The experimental animals were subjected to a behavioral tests (Kong test), and the levels of noradrenaline, serotonin, and cortisol were determined in their blood plasma. The results of the behavioral test revealed that most dogs exhibited increased activity of the left hemisphere. Furthermore, irrespective of the sex and paw preference, stroking the animal was found to alleviate the stress response, which was reflected in reduced cortisol levels and increased serotonin levels. It was found that the plasma noradrenaline, cortisol, and serotonin levels were lower in the female dogs than in the males. Additionally, the plasma noradrenaline and serotonin levels were higher in the right-pawed dogs than in the left-pawed dogs. The present results confirm the assumption that right-pawed dogs adapt to stressful conditions more readily.